Penerapan Foot Massage Terhadap Penurunan Tekanan Darah Pada Penderita Hipertensi Di RSUD Kabupaten Karanganyar - Ervianda Ervianda; Hermawati Hermawati; Dwi Yuningsih (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Background: Hypertension is a health problem in all parts of the world and one of the main risk factors for cardiovascular disease. It is estimated that 1.28 billion adults aged 30-79 years worldwide suffer from hypertension as well as the Karanganyar District Hospital where there have been 889 cases with hypertension since the last 1 year. One of the non-pharmacological therapies that can be used for hypertension is foot massage. Foot massage is one of the complementary therapies currently used for hypertension. Objective: To find out the results of the implementation of giving foot massage to reducing blood pressure in 2 respondents with hypertension at the Karanganyar Regency Hospital. Methods: Using a descriptive method with a case study design approach, respondents used 2 hypertensive patients. Determination of respondents according to the inclusion and exclusion criteria was carried out for 3 days. Foot massage and blood pressure measurement using a sphygmomanometer Results: Providing foot massage was able to reduce blood pressure in 2 respondents at the Karanganyar District Hospital Conclusion: There were changes in 2 respondents after foot massage was carried out for 3 days at the Karanganyar District Hospital.